Simplify the expression below.
![Simplify the expression below class=](https://us-static.z-dn.net/files/d49/75147ac1c925c91d0e4443a09aca5ead.png)
Answer:
[tex] \frac{(x + 1 )}{5 x} [/tex]
Step-by-step explanation:
[tex] \frac{ {x}^{2} - 8x - 9 }{5 {x}^{2} - 45x } \\ \\ = \frac{ {x}^{2} - 9x + x - 9 }{5 x({x} - 9) } \\ \\ = \frac{ x({x} - 9) + 1(x - 9 )}{5 x({x} - 9) } \\ \\ = \frac{ ({x} - 9) (x + 1 )}{5 x({x} - 9) } \\ \\ = \frac{(x + 1 )}{5 x} \\ [/tex]
Answer:
Hello,
[tex]\frac{x+1}{5x}[/tex]
with x ≠ 9
Step-by-step explanation:
a² - b² = (a + b) (a - b)
x² - 8 x - 9 = (x - 4)² - 16 - 9 = (x - 4)² - 25 = (x - 4)² - 5² = (x - 4 + 5) (x - 4 - 5)
= (x + 1) (x - 9)
5 x² - 45 x = 5 x (x - 9)
[tex]\frac{x^{2} - 8 x-9}{5x^{2} -45x} = \frac{(x+1)(x-9)}{5 x (x-9)} = \frac{x+1}{5x}[/tex]
with x ≠ 9 because (x - 9) ≠ 0